2014
DOI: 10.1128/aem.03580-13
|View full text |Cite
|
Sign up to set email alerts
|

Zebrafish as a Natural Host Model for Vibrio cholerae Colonization and Transmission

Abstract: The human diarrheal disease cholera is caused by the aquatic bacterium Vibrio cholerae. V. cholerae in the environment is associated with several varieties of aquatic life, including insect egg masses, shellfish, and vertebrate fish. Here we describe a novel animal model for V. cholerae, the zebrafish. Pandemic V. cholerae strains specifically colonize the zebrafish intestinal tract after exposure in water with no manipulation of the animal required. Colonization occurs in close contact with the intestinal epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
97
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 91 publications
(106 citation statements)
references
References 48 publications
7
97
0
Order By: Relevance
“…Previous work in our laboratory confirmed this finding in zebrafish infected with V. cholerae. We found that in time course experiments, zebrafish infected with classical strain O395 remained highly colonized only for about 24 h postinfection and were cleared by 72 h postinfection (18). However, as we have also demonstrated in this study, zebrafish infected with the El Tor strain remained robustly colonized for at least 144 h postinfection, or 6 days.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Previous work in our laboratory confirmed this finding in zebrafish infected with V. cholerae. We found that in time course experiments, zebrafish infected with classical strain O395 remained highly colonized only for about 24 h postinfection and were cleared by 72 h postinfection (18). However, as we have also demonstrated in this study, zebrafish infected with the El Tor strain remained robustly colonized for at least 144 h postinfection, or 6 days.…”
Section: Discussionsupporting
confidence: 80%
“…Fish were observed to have diarrhea even when infected with ΔtoxT strains of V. cholerae that do not produce cholera toxin, which suggests that there are other factors responsible for inducing diarrhea in infected fish (18). Accessory toxins are the most likely cause of this noncholera diarrhea.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with those using mammalian animal models, studies with soft-shelled turtles provide a new method for evaluating V. cholerae colonization on aquatic animal surfaces; animals can be continuously observed without euthanization. In addition, zooplankton, fish, shellfish, chironomid egg masses, waterfowl, and crustaceans are environmental hosts of V. cholerae (6,(38)(39)(40)(41)(42)(43), and fish and shellfish are proven vectors of V. cholerae (44). In studies of colonization in aquatic organisms, soft-shelled turtles can be anesthetized and sampled out of water for relatively long periods without the risk of hydropenia and death, due to their amphibious nature, making them a better model than zebrafish and other fish or shrimp models.…”
Section: Discussionmentioning
confidence: 99%
“…Zebrafish (Danio rerio) have been established as an aquatic host which can be colonised and infected by V. cholerae in a concentration dependent manner, and infection eventually leads to mortality. [46][47][48] Zebrafish are a suitable natural host model for V. cholerae colonisation and transmission as their gastrointestinal development and physiology closely mimics that of mammalian organisms. 49 Additionally, ease of propagation and live imaging made them a good choice of host for our in vivo studies, in particular at this early .…”
Section: Cc-by 40 International License Not Peer-reviewed) Is the Aumentioning
confidence: 99%